Familial T-cell non-Hodgkin lymphoma caused by biallelic MSH2 mutations. Issue 7 (29th June 2007) - Scott, Richard H; Homfray, Tessa; Huxter, Nicola L; Mitton, Sally G; Nash, Ruth; Potter, Mike N; Lancaster, Donna; Rahman, Nazneen
Abstract : Familial non-Hodgkin lymphoma (NHL) is rare and in most cases, no underlying cause is identifiable. We report homozygous truncating mutations in the mismatch repair gene MSH2 (226C→T; Q76X) in three siblings who each developed T-cell NHL in early childhood. All three children had hyperpigmented and hypopigmented skin lesions. Constitutional biallelic MSH2 mutations have previously been reported in five individuals, all of whom developed malignancy in childhood. Familial lymphoma has not been reported in this context or in association with biallelic mutations in the other mismatch repair genes MLH1, MSH6 or PMS2 . In addition, hypopigmented skin lesions have not previously been reported in biallelic MSH2 carriers. Our findings therefore expand the spectrum of phenotypes associated with biallelic MSH2 mutations and identify a new cause of familial lymphoma. Moreover, the diagnosis has important management implications as it allows the avoidance of chemotherapeutic agents likely to be ineffective and mutagenic in the proband, and the provision of cascade genetic testing and tumour screening for relatives.